(untitled) (Research, Society and Development, 2020)
The work overload permeates as constant subjects of debates, causing damage to both professionals and assisted patients. In view of the relevance of the theme, the work aims to: reflect and discuss current perspectives in the context of the assessment of the burden on the nursing team and the impact on the quality of care provided to patients. Theoretical-reflective, descriptive study with a qualitative approach, which was built through the bibliographic exploration of the theme. After reading, two guiding axes were designated to reflect on the theme. It is observed that there is the implementation of health policies related to the theme, as well as instruments that can assist in the assessment of the burden, but it appears that there is a need for a look directed at the worker and his needs, because the burden is associated with losses in terms of patient safety and quality of care. Therefore, it is observed that for a good assistance, with the minimum acceptable errors, it is necessary to hospital institutions that promote working conditions, with efficiency in physical and human resources and cohesive institutional processes for a safe exercise.